A STUDY OF THE RELATIONSHIP BETWEEN THE OCTANE NUMBER AND THE CHEMICAL COMPOSITION OF REGULAR, MIDGRADE, AND PREMIUM GASOLINE - Fanar M. Bamerni (Science Journal of University of Zakho, 2024)
The present  study was conducted at Zakho City in Northern Iraq to evaluate three different types of gasoline: Regular, Midgrade, and Premium. These types of gasoline are categorized based on their octane rating, which was measured to verify their classification. The results showed that the initial classification was accurate, with respective values of 87.5, 89.8, and 91.1. The  study evaluated the three grades of gasoline available  at Zakho Gas Stations in Northern Iraq, including Regular, Midgrade, and Premium. The study  also compared the chemical composition of the three gasoline grades in terms of aromatics, olefin, sulfur content, and oxygen content. All the three gasoline grades met the American Society for Testing and Materials (ASTM) standard for chemical composition, and all had acceptable specific gravities. However, Midgrade gasoline is not recommended for use during the summer due to its high Reid vapor pressure (RVP) value, low Initial boiling point (IBP), and final boiling point( FBP). In general, the  study showed that the Regular and Premium gasoline types sold in North  of Iraq meet international quality standards. However, Midgrade gasoline is not recommended for use during the summer due to its high RVP value, low IBP, and FBP, which can lead to increased volatility and environmental pollution,